If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k(k + 3) = -19 Reorder the terms: 4k(3 + k) = -19 (3 * 4k + k * 4k) = -19 (12k + 4k2) = -19 Solving 12k + 4k2 = -19 Solving for variable 'k'. Reorder the terms: 19 + 12k + 4k2 = -19 + 19 Combine like terms: -19 + 19 = 0 19 + 12k + 4k2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. 4.75 + 3k + k2 = 0 Move the constant term to the right: Add '-4.75' to each side of the equation. 4.75 + 3k + -4.75 + k2 = 0 + -4.75 Reorder the terms: 4.75 + -4.75 + 3k + k2 = 0 + -4.75 Combine like terms: 4.75 + -4.75 = 0.00 0.00 + 3k + k2 = 0 + -4.75 3k + k2 = 0 + -4.75 Combine like terms: 0 + -4.75 = -4.75 3k + k2 = -4.75 The k term is 3k. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3k + 2.25 + k2 = -4.75 + 2.25 Reorder the terms: 2.25 + 3k + k2 = -4.75 + 2.25 Combine like terms: -4.75 + 2.25 = -2.5 2.25 + 3k + k2 = -2.5 Factor a perfect square on the left side: (k + 1.5)(k + 1.5) = -2.5 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 3-2=x+4 | | 5x+2(x+2)=18 | | 6x^2+11x=72 | | 4x^2-44x=-120 | | 3x+6=X+4 | | C=2500+0.5Yd | | 14+8.2= | | -2j+5=6h | | 3u-(25-u)=-11-2u | | Y=3mx-4b | | t^4-13t^2+36=0 | | (x-1)(2x+1)=0 | | 320=24+20 | | x^2+28x+5=0 | | y^2+16y+28=0 | | 6x^2-9-13x^2+11+11x= | | 3p+3=14 | | 12+(34-5)= | | 3(x+8)=15 | | -16x=-48 | | 5x^2-5=0 | | x-3x=8 | | 8x-9=7x-3 | | 9.4m= | | 0.5(3x+2)-0.2(x+6)=5 | | 0.33(2x+3)-0.2(x+6)=4 | | 3(n-9)=30 | | 12(x+3)=3(4x+5)+21 | | 3x^4=16x^2+12 | | 0.5(x+2)=0.25(2x+4) | | 0.2(4x+7)=3(4-4x)+15 | | 14m-2=2(8m-5) |